Essays on the economic burden of animal diseases - Tozooneyi, Takesure (My University, 2024)
Essay 1: The potential economic welfare effects of African Swine Fever on the U.S. swine supply chain African Swine Fever (ASF) is a deadly viral disease of swine that often leads to substantial economic losses due to the death of animals, the cost of control measures, and loss of trade. The U.S. pork sector, a major component of the agricultural economy, remains vulnerable to ASF. Although the disease has never been detected in the United States, understanding its potential economic impacts is crucial for preparing and prioritizing animal health investments. Using an Equilibrium Displacement Model (EDM) adapted to incorporate the cull hog sector and live hog trade, we quantify the economic welfare impact of hypothetical ASF outbreaks under varying supply, demand, and export shock scenarios. Our analysis reveals that the potential economic losses vary significantly depending on the severity of the outbreak and the resulting market shocks. Small outbreaks confined to specific regions may result in moderate welfare declines, while large-scale outbreaks with substantial export losses could have severe economic impacts across the entire supply chain. The analysis indicates losses ranging from $277 million to $4,077 million across four quarters, primarily driven by losses in the weaner and feeder pig segments. These findings underscore the importance of strengthening biosecurity measures, diversifying export markets, and developing rapid response protocols to mitigate the adverse effects of ASF. Essay 2: How Important are Trade Agreements during Poultry Disease Events? In recent times, international trade in livestock and livestock products has witnessed remarkable growth, driven by rising global demand for animal-sourced foods. However, contagious animal diseases are increasingly influencing trade volumes and patterns. Bilateral frameworks, such as Trade Agreements (TAs), can be crucial in smoothening trade during animal health crises. This study examines the role of TAs in mitigating the trade effects of Highly Pathogenic Avian Influenza (HPAI) and Newcastle Disease (ND) on poultry trade. Utilizing a comprehensive dataset of 212 countries engaged in poultry trade, we employed panel gravity models to assess the role of TAs. The results show that while TAs generally promote trade, they do not mitigate the contemporaneous effects of HPAI on poultry trade, but they do for ND. Product-specific analysis reveals heterogeneity in how TAs help sustain trade during outbreaks of both HPAI and ND. Moreover, TA members experience a quicker rebound in trade following disease events. These findings emphasize the importance of TAs in enhancing the resilience of international trade networks during animal health emergencies.
Keywords: African Swine Fever (ASF); Economic welfare impact; Equilibrium Displacement Model (EDM); Poultry disease events; Trade Agreements (TAs); Animal health crises